2020
DOI: 10.3126/jcmc.v10i1.28073
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and sonohysterography evaluation of infertile women

Abstract: Background: Hysterosalpingography (HSG) is an integral part of the Conventional clinical evaluation of infertile women. Now a day, Sonohysterography is a modern technique widely used in the clinical evaluation. The objective of this study was to identify pelvic pathology; compare the effect and findings of tubal patency test between Sonohysterosalpingography and single film HSG radiograph.Methods: This is a prospective evaluation of infertile women who attended the infertility unit of the gynecology department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The pathological findings stated that polycystic ovaries were found in 15%, endometrial polyps in 2 cases, fibroid uterus 5%, ovarian cysts in 2%, and uterine cysts with hydrosalpinx in 4%. 11 In another study of 98 cases, SIS/SHG showed abnormal uterine findings in 27% of cases, and HSG detected abnormal uterine findings in 11% of cases, adhesions were found in 12%, fibroid in 8%, polyp in 5%, septate/ bicornuate uterus in 1% cases. 12 Another study narrated a total of 24 infertile women, where 87.5% of women had suffered from primary infertility and 12.5% from secondary infertility level.…”
Section: Discussionmentioning
confidence: 90%
“…The pathological findings stated that polycystic ovaries were found in 15%, endometrial polyps in 2 cases, fibroid uterus 5%, ovarian cysts in 2%, and uterine cysts with hydrosalpinx in 4%. 11 In another study of 98 cases, SIS/SHG showed abnormal uterine findings in 27% of cases, and HSG detected abnormal uterine findings in 11% of cases, adhesions were found in 12%, fibroid in 8%, polyp in 5%, septate/ bicornuate uterus in 1% cases. 12 Another study narrated a total of 24 infertile women, where 87.5% of women had suffered from primary infertility and 12.5% from secondary infertility level.…”
Section: Discussionmentioning
confidence: 90%
“…It can cause transient distortion of the endometrial cavity by blood, mucous, debris and air bubbles which can cause false positive results [12]. Sonohysterography, a modern technique, now widely used for evaluation of female infertility is more sensitive than TVS, less expensive than hysteroscopy and has a comparable diagnostic accuracy [7].…”
Section: Introductionmentioning
confidence: 99%
“…The methods available for the assessment of endometrial cavity and tubal patency include HSG, TVS, Laparoscopic chromopertubation, Falloposcopy, radionuclide hysterosalpingography (7). Among the less invasive or noninvasive diagnostic modalities are ultrasonography, Sonosalphingography and MRI while invasive modalities are HSG, hysteroscopy and laparoscopy (8).…”
Section: Introductionmentioning
confidence: 99%